Interleukin-35 levels in patients with stable coronary artery disease - Oflar, Ersan; Şahin, Mustafa Hakan; Demir, Bülent; Ertuğrul, Abdulcelil Sait; Öztaş, Didem Melis; Beyaz, Metin Onur; Uğurlucan, Murat; Turhan Çağlar, Fatma Nihan (Arquivos Brasileiros de Cardiologia, 2022)
Background: It has been shown that interleukin-35 (IL-35) subunits are strongly expressed in atherosclerotic plaques in humans. Therefore, it is considered to play a role in atherosclerosis. Objectives: In this study, IL-35 levels were compared with the control group in patients with stable coronary artery disease (CAD), and the association between IL-35 levels and the lesion type, lesion severity and extension was investigated with the Gensini score (GS) and the Syntax score (SS) in the patient group. Methods: Sixty patients (18 female and 42 male) with CAD diagnosed by coronary angiography, who presented with typical chest pain and positive noninvasive cardiac stress test, and 46 patients (18 female and 28 male) with normal coronary lumenogram, were included in this study. Gensini and Syntax scores were calculated in the patient group, and these values were compared with IL-35 levels. Non-normally distributed variables were analyzed by the Mann-Whitney U test, whereas normally distributed parameters were assessed by Student’s t-test. The difference between categorical variables were evaluated by the Chi-square or Fisher test. P-values<0.05 were considered as statistically significant. Results: No significant differences were observed between patients and the control group in terms of demographic characteristics and laboratory findings. Compared to the control group, IL-35 levels of the CAD group were considerably lower (36.9±63.9 ng/ml vs. 33.2±13.2 ng/ml, p<0.008). Although not statistically significant, IL-35 levels were higher in patients with low SS than among those with high SS (33.2±13.7 vs. 31.8±8.9, p=0.51). The IL-35 values of the patients with high GS were significantly lower than in patients with low GS (35±17.4 vs. 30.7±8.6, p=0.043). Conclusion: It has been shown that IL-35 levels can be a new biomarker for stable CAD, and IL-35 is associated with the extension of CAD.
Níveis de ınterleucina-35 em pacientes com doença arterial coronariana estável
Keywords: Atherosclerosis; Coronary Artery Disease; Gensini Score; Interleukin-35; Syntax Score